Me Possessed? Interpreting Spirit Possession through Ethnographic Reflexivity. An Afro-Honduran Case Study - Perdomo, Marcela (AM. Rivista della Società Italiana di Antropologia Medica, 2022)
Me Possessed? Interpreting Spirit Possession Through Ethnographic Reflexivity. An Afro-Honduran Case Study This Article explores the conditions of ethnographical knowledge production during my fieldwork on spirit possession in Dugu, the religion practiced by the Garifuna, an Afro-Amerindian community of northern Honduras. Drawing on my journey from novice to potential priestess, but also from an ethnographer to anthropologist, I will argue the validity of putting my own body and subjectivity in favor of full participation as a powerful ethnographical tool to approach this phenomenon. The kind of anthropological investigation that I defend in this paper is neither a strictly native religious perspective, neither a cold distant scientific analysis. Instead, I will give close attention to the interplay of the Garifuna’s practice of spirit possession and my own experience of possession as it was interpreted by my hosts. My intention here, is to show that my personal involvement in a possession-based religion worked as a meaning mediator to phenomena difficult to grasp solely from an intellectual and outsider’s perspective. Io posseduta? Un’interpretazione della possessione spiritica attraverso la riflessività etnografica. Un caso di studio afro-honduregno Questo articolo esplora le condizioni della produzione di conoscenza etnografica durante il mio lavoro sul campo sulla possessione spiritica nel Dugu, la religione praticata dai Garifuna, una comunità afro-amerindiana dell’Honduras settentrionale. Attingendo al mio viaggio da novizia a potenziale sacerdotessa, ma anche da etnografa ad antropologa, sosterrò la validità di mettere il mio corpo e la mia soggettività a favore della piena partecipazione come potente strumento etnografico per approcciare questo fenomeno. Il tipo di indagine antropologica che difendo in questo articolo non è né una prospettiva religiosa strettamente autoctona, né una fredda analisi scientifica a distanza. Invece, presterò molta attenzione all’interazione tra la pratica della possessione spiritica dei Garifuna e la mia esperienza personale di possessione come è stata interpretata dai miei ospiti. La mia intenzione è quella di mostrare che il mio coinvolgimento personale in una religione basata sulla possessione ha funzionato come un mediatore di significato per fenomeni difficili da cogliere solo da una prospettiva intellettuale ed esterna.